Remun language use and maintenance - Peter F. Cullip (Journal of Modern Languages)
The Remun lban community of Sarawak speak a dialect of Iban which is said to be unintelligible to other Ibans. Generally, they possess a strong identity as Remun and this code is the essence of their community identity vis-a-vis the Iban and neighboring ethnic groups. For many Remun villages. This situation is changing. As a relatively small and linguistically isolated group, the multilingual Remun are facing strong macro-pressure which could be expected to lead to language shift to Iban. This is indeed happening in peripheral villages. This paper reports on the linguistic situation in the original, core Remun settlement of Kampung Remun and concludes that micro-level factors are operating to maintain the use and inter-generational transmission of Remun in this village.